2021
DOI: 10.3390/jcm10215151
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts in Humeral Component Design for Anatomic and Reverse Shoulder Arthroplasty

Abstract: The history of humeral component design has evolved from prostheses with relatively long stems and limited anatomic head options to a contemporary platform with short stems and stemless implants with shared instrumentation and the ability to provide optimal shoulder reconstruction for both anatomic and reverse configurations. Contemporary humeral components aim to preserve the bone, but they are potentially subject to malalignment. Modern components are expected to favorably load the humerus and minimize adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Standard length stems were sized to extend 33% of the diaphysis and were traditionally used with good performance and survivorship. 19 , 21 By utilizing a stem which extends to the cylindrical section of the diaphysis (the TP), the implant stability is increased and the standard length stem reduces the risk of malalignment as reported with short-stem prostheses. 1 , 9 This reduction in malalignment could be achieved with a short-stem prosthesis which also extended beyond the TP described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Standard length stems were sized to extend 33% of the diaphysis and were traditionally used with good performance and survivorship. 19 , 21 By utilizing a stem which extends to the cylindrical section of the diaphysis (the TP), the implant stability is increased and the standard length stem reduces the risk of malalignment as reported with short-stem prostheses. 1 , 9 This reduction in malalignment could be achieved with a short-stem prosthesis which also extended beyond the TP described in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse total shoulder arthroplasty (RSA) is a well-established and increasingly utilized procedure for improving pain relief and function in patients with rotator cuff insufficiency and glenohumeral osteoarthritis. 40 In recent years, periprosthetic scapular spine fractures (SSF) and acromial fractures (AF) have been recognized as a unique complication of RSA. 11 , 28 Biomechanical investigations have suggested etiologies for these fractures to include alterations in deltoid strain, 21 , 41 , 50 glenoid baseplate screws as potential stress risers, 20 and variations in implant and arm positioning.…”
mentioning
confidence: 99%
“…Modifications to humeral component design have evolved over the years, with efforts focused on reducing rates of scapular notching and addressing range-of-motion (ROM) deficits that were common with traditional Grammont style inlay prostheses. 40 Early biomechanical studies by Virani et al 46 suggested that ROM deficits and impingement seen with the Grammont style prosthesis were primarily related to implant positioning, with humeral implant design (inset vs. onset) having little impact. 46 These findings led Dr. Frankle and their group to modify the principles of reverse shoulder arthroplasty in order optimize soft tissue tension and ROM.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, shorter stems have been introduced with the purported advantages of easy revisability and less stress shielding. 9 Finally, newer stemless implants have also been designed to minimize diaphyseal instrumentation and preserve the bone. The implications of humeral implant design (anatomic or reverse; or standard-length, short-stem, or stemless implant) on the management of periprosthetic humeral fractures have not been explored in detail (Figure 1).…”
mentioning
confidence: 99%